De novo hepatocellular carcinoma in living donor liver grafts: A Japanese multicenter experience. Issue 12 (27th September 2020) - Goto, Ryoichi; Kosai‐Fujimoto, Yukiko; Yagi, Shintaro; Kobayashi, Tsuyoshi; Akamatsu, Nobuhisa; Shimamura, Tsuyoshi; Imura, Satoru; Ogiso, Satoshi; Mizuno, Shugo; Takatsuki, Mitsuhisa; Fukuhara, Takasuke; Kanto, Tatsuya; et al.
Abstract : Aim: Direct‐acting antivirals for hepatitis C virus have reduced the decompensation risk. Immunosuppressants for transplantation raise the risk of occurrence of de novo malignancies. We assessed the probabilities of and risk factors for de novo hepatocellular carcinoma (HCC) development post‐living donor liver transplantation (LDLT). Methods: We retrospectively evaluated the data of developed HCC in a graft including metastatic HCC post‐LDLT from 2779 adult cases collected from nine major liver transplantation centers in Japan. Results: Of 2779 LDLT adult recipients, 34 (1.2%) developed HCCs in their grafts. Of 34, five HCCs appeared to be de novo because of a longer period to tumor detection (9.7 [6.4–15.4] years) and no HCC within the native liver of the two recipients. The donor origin of three of five de novo HCCs was confirmed using microsatellite analysis in resected tissue. Primary disease of all five was hepatitis C virus‐related cirrhosis, of which two were treated with direct‐acting antivirals. Four of five developed HCC de novo in the hepatitis B core antibody‐positive grafts. De novo HCCs had favorable prognosis; four of five were cured with complete remission. However, recurrent HCC ( n  = 29) in the graft had a poorer outcome, especially in patients with neutrophil to lymphocyte ratio scores above 4 (median survival time, 262 [19–463] days). Conclusion: Analysis of the database from major liver transplantation institutes in Japan revealed that de novo HCCs determined by microsatellite analysis were rarely detected, but the majority were successfully treated. LDLT recipients with higher risks of de novo HCC, including those with hepatitis B core antibody‐positive grafts, should be carefully followed by surveillance of the liver graft.